1974
DOI: 10.1159/000260114
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries in Phenylketonuric Children

Abstract: Phenylketonuria is a rare inherited metabolic defect in which there is a deficiency of the liver enzyme phenylalanine hydroxylase. Unless this condition is diagnosed within the first few weeks of life, and treated with special diets which have a high carbohydrate content, but which are very low in phenylalanine, severe mental deficiency can result. 105 phenylketonuric (PKU) children, aged 10 months to 16 years, were examined to determine whether this special diet had any effect on the prevalence of caries in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…5 Kilpatrick et al 12 compared 40 PKU patients with healthy children and reported a 17% prevalence of dental caries in PKU patients, which was similar to healthy individuals. Although in our study, the incidence and prevalence of caries were not investigated, we showed that the DMFT in PKU patients was not substantially higher than in the control group, so it can be concluded that the results of our study are not different from the study of Kilpatrick et al 12 In another study, Winter et al 15 concluded that the presence of caries in 105 children with PKU was similar to healthy children, which also confirms our results. In contrast to these results, a high-fat and carbohydrate-rich diet is expected to exacerbate tooth decay in PKU patients.…”
Section: Discussionsupporting
confidence: 87%
“…5 Kilpatrick et al 12 compared 40 PKU patients with healthy children and reported a 17% prevalence of dental caries in PKU patients, which was similar to healthy individuals. Although in our study, the incidence and prevalence of caries were not investigated, we showed that the DMFT in PKU patients was not substantially higher than in the control group, so it can be concluded that the results of our study are not different from the study of Kilpatrick et al 12 In another study, Winter et al 15 concluded that the presence of caries in 105 children with PKU was similar to healthy children, which also confirms our results. In contrast to these results, a high-fat and carbohydrate-rich diet is expected to exacerbate tooth decay in PKU patients.…”
Section: Discussionsupporting
confidence: 87%
“…In one of the two there were no controls and in the other the use of a sibling control group meant that there was no matching for age or sex. In the one British study carried out in 1974, 105 children with PKU were examined and their mean dmf compared with national ®gures current at the time [19]. This study con®rmed the ®ndings of the two previous ones in that the dmf of these children was not signi®cantly dierent to that of the normal population.…”
Section: Cariessupporting
confidence: 66%
“…As PKU is a relatively rare genetic disorder, the sample of PKU children, as compared to the diabetic and healthy group, was small. All other studies assessing the oral health of children with PKU had similar or smaller sample sizes [4,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the dental status and oral health of children with PKU are few and far between. All studies have revealed similar or lower caries experience in PKU children despite their known use of highly acidic supplements and a diet rich in carbohydrates [4,[19][20][21][22] ( Table 4). Some of the authors have attributed the reported caries-related findings to the use of fluoride supplements and water fluoridation.…”
Section: Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation